VD_FINDINFO Arrêt / 2012 / 931 vom 4. Dezember 2012 - VD Tribunal cantonal (2012)
TUTELLE, NULLITÉ, DROIT D'ÊTRE ENTENDU, RÉSIDENCE HABITUELLE, ADMISSION DE LA DEMANDE | 369 CC, 374 CC, 379 CPC, 393 CPC, 30 al. 1 Cst., 85 al. 2 LDIP, 5 al. 1 CLaH 2000, 5 al. 2 CLaH 2000